2015
DOI: 10.3945/jn.115.218297
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Whey Protein Supplementation Did Not Enhance Muscle Mass and Physical Function in Well-Nourished Healthy Older Postmenopausal Women

Abstract: This study showed that in protein-replete, healthy, ambulant, postmenopausal older women, 30 g/d of extra protein did not improve the maintenance of muscle mass or physical function despite evidence of deterioration in muscle measurements in the upper limb. This trial was registered at the Australian New Zealand Clinical Trials Registry as ACTRN012607000163404.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 26 publications
4
90
0
Order By: Relevance
“…Some studies [11, 37, 38] have demonstrated a beneficial effect of nutritional supplementation independent of exercise on muscle strength, physical function, and lean mass in older adults, but others have not [39, 40]. This discrepancy may, in part, be explained by a heterogeneity of response to supplementation in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [11, 37, 38] have demonstrated a beneficial effect of nutritional supplementation independent of exercise on muscle strength, physical function, and lean mass in older adults, but others have not [39, 40]. This discrepancy may, in part, be explained by a heterogeneity of response to supplementation in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates, 1137 identified articles remained of which 1068 were excluded during review of title and abstract (FIGURE 1). Full texts of the remaining 69 articles were obtained and assessed, yielding eight applicable articles for the meta-analysis [11,12,15,16,[21][22][23][24]. In total, we received individual participant data from six articles, which was used for the individual participant data analysis [11,12,15,[21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…In the pooled dataset (n=486), the mean age at baseline was 74.9 ± 5.1 years and 72.4% (n=352) of the participants was female. Participants in the pooled analysis were healthy (n=282) [11,21,23], sarcopenic (n=78) [22], frail (n=65) [15], diabetic (n=67) [12,22] or had cancer (n=1) [23]. The two studies that were not integrated in the pooled analysis, since we were unable to receive the data, were conducted in healthy females [16] and residential care habitants [24].…”
Section: Participantsmentioning
confidence: 99%
“…These observations validated our experimental design to analyze the effect of various protein supplementations in a rodent model of aging. While the rats had free access to food, they were fed with a low-protein standard diet (10% by weight of protein, instead of the normal protein diet at 16%), since previous studies regarding aging have highlighted the ineffectiveness of protein supplementation in subjects who had adequate energy, nutrient, and protein intakes [3941]. Furthermore, in light of previous reports showing that ingestion of a nutritional supplement immediately after exercise can improve the net protein balance [42, 43], with stimulation of skeletal muscle protein synthesis [44], boluses as free access drinking solution were given immediately following the treadmill sessions.…”
Section: Discussionmentioning
confidence: 99%